Republic of Kosovo : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Kosovo. (IMF Staff Country Reports; Country Report ;, 2018)
This 2017 Article IV Consultation highlights that Kosovo has made significant progress since the 2015 Article IV consultation in ensuring fiscal discipline and strengthening the financial sector. The fiscal deficit has been kept well below the 2 percent of GDP fiscal rule ceiling, government bank balances are now above the minimum level of 4.5 percent of GDP, and public debt remains low. Banks remain healthy and credit growth has increased. Notwithstanding, important structural challenges remain. Although medium-term growth is now projected at about 4 percent, more and better growth is needed to accelerate income convergence with the European Union and reduce inequality. The fiscal deficit is expected to remain within the fiscal rule while accelerating the investment financed by international financial institutions.